Analisis Persediaan Bahan Baku pada Usaha Mete di Kota Kendari (Studi Kasus pada UD. Mete Mubaraq Lombe) - Sucitra, Sahrani; Zani, Munirwan; Yusria, Wa Ode (Department of Agribusiness, Halu Oleo University, 2019)
This research aims to know the inventory of raw cashew nuts peeled on UD. Mete Mubaraq Lombe of the year 2017; Analyze the efficiency of the inventory of raw materials according to the EOQ method on UD. Mete Mubaraq Lombe; determine the Safety Stock and Reorder Point at UD. Mete Mubaraq Lombe. The study was designed as a case study of using primary data and secondary data, variables in this study include a Total Inventory Cost, Ordering Cost and Carrying Cost. There were some of the results obtained in this study. First, the type of raw materials used is cashew nuts peeled from Region Lombe by way of partnering. The volume of purchase of raw materials over the past year as many as 52,000 kg. Booking fees during the year 2017 are Rp 43,872,000. Storage costs during the year 2017 are Rp 48,144,000. Secondly, the supply of raw materials of peeled cashew nuts more efficiently by using the EOQ method. It can be seen from the difference in TIC companies issued in the year 2017 is Rp. 45,878,000.4 while the EOQ method based on the TIC of Rp 18,762,434.4. So the difference in TIC is Rp. 27,115,566. Thirdly, in order not to run out of stock in the warehouse, then the safety stock that must always be available in the company as much as 1,459.26 kg and company do a reorder point when the raw materials in the warehouse as much as 1,690.46 kg.